2000
DOI: 10.1152/ajpcell.2000.279.2.c295
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strain-induced Ca2+waves are propagated via ATP release and purinergic receptor activation

Abstract: Mechanical strain applied to prostate cancer cells induced an intracellular Ca(2+) (Ca(i)(2+)) wave spreading with a velocity of 15 microm/s. Ca(i)(2+) waves were not dependent on extracellular Ca(2+) and membrane potential because propagation was unaffected in high-K(+) and Ca(2+)-free solution. Waves did not depend on the cytoskeleton or gap junctions because cytochalasin B and nocodazole, which disrupt microfilaments and microtubules, respectively, and 1-heptanol, which uncouples gap junctions, were without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
105
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 47 publications
(34 reference statements)
2
105
0
Order By: Relevance
“…Results from previous studies suggest that calcium signaling in chondrocytes occurs via stretch activated calcium channels 14,43 and/or via stretch activated release of ATP. [44][45][46][47][48] In order to investigate these possible mechanotransduction pathways, we plan to perform studies in which stretch activated calcium channels are inhibited by gadolinium and intracellular calcium release is inhibited via thapsigargin. 30,44,45 Calcium signaling occurred faster and had higher amplitudes at 378C than at 218C, indicating that Ca 2þ signaling is temperature dependent, as has been found for other cell types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from previous studies suggest that calcium signaling in chondrocytes occurs via stretch activated calcium channels 14,43 and/or via stretch activated release of ATP. [44][45][46][47][48] In order to investigate these possible mechanotransduction pathways, we plan to perform studies in which stretch activated calcium channels are inhibited by gadolinium and intracellular calcium release is inhibited via thapsigargin. 30,44,45 Calcium signaling occurred faster and had higher amplitudes at 378C than at 218C, indicating that Ca 2þ signaling is temperature dependent, as has been found for other cell types.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46][47][48] In order to investigate these possible mechanotransduction pathways, we plan to perform studies in which stretch activated calcium channels are inhibited by gadolinium and intracellular calcium release is inhibited via thapsigargin. 30,44,45 Calcium signaling occurred faster and had higher amplitudes at 378C than at 218C, indicating that Ca 2þ signaling is temperature dependent, as has been found for other cell types. 34,35 This finding may have significant functional implications as cartilage is an avascular tissue known to change temperature significantly when exposed to ambient temperature changes 49,50 which, according to our results, may affect the ability of chondrocytes to respond to mechanical stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that P2 activation leads to increases in concentration of intracellular calcium and PGE2 release (Naemsch et al, 2001). ATP, which activates this pathway, is typically released by bone, endothelial and epithelial cells and fibroblasts under stress conditions, acting as a DAMP/alarmin (Bodin & Burnstock, 1998;Burnstock, 1999;Furuya, Sokabe & Furuya, 2005;Grygorczyk & Hanrahan, 1997;John & Barakat, 2001;Katsuragi & Migita, 2004;Katz, Boland & Santillan, 2006;Kerkweg & de Groot, 2005;Milner et al, 1992;Milner et al, 1990b;Ohata et al, 1997;Patel et al, 2005;Romanello et al, 2001;Sauer, Hescheler & Wartenberg, 2000;Yamamoto et al, 2003).…”
Section: P2x7 Receptor: a Possible Mediator Of Orthodontic Mechanotramentioning
confidence: 99%
“…Because mechanical stretch can induce cellular ATP release (14,15), P 2 receptors might be stimulated by stretch. Since, in preliminary work, we have shown that ATP inhibits ENaC activity in A6 distal nephron cells, we hypothesized that the inhibitory effect of stretch-induced ATP release on ENaC might obscure a stretch-induced ENaC activation.…”
mentioning
confidence: 99%